Impact of Anchor Borrower Programme on the productivity of beneficiaries in the selected local government areas of Niger State, Neigria (NTU Journal of Agriculture and Veterinary Science, 2025)
The study assessed the impact of ABP on rice farmers’ yield in Niger State, Nigeria. Objectives of the study are to: identify the farmers’ sources of information and determine the impact of ABP on farmers. A total of 138 farmers were randomly selected. Data was analysed using descriptive, correlation, t-test, and regression analyses. OLS result showed a significant relationship existed between beneficiaries’ farming experience (ß = 19.23, p?0.01), farm size (ß = 17.01, p?0.05), (ß = 1.07, p?0.03) and productivity. Also, there was significant difference between the beneficiaries’ productivity before and after the introduction of ABP. It was concluded that there is a causal relationship between farming experience, farm size, credit accessibility and farmers’ productivity, and that ABP had a positive effect on the rice farmers’ productivity. The study recommended that more information and enlightenment should be given concerning ABP, and that the programme should be given better supervision.